Speech-Language Therapy Interventions in Childhood Apraxia of Speech Aimed at Developing Functional Communication: a Scoping Review - Herrán-Landeros, Carolina; Schnitzler Sommerfeld, Nicole; Camila; Lagrutta Diaz, Laura; Perez Maulen, Catalina (Revista Chilena de Fonoaudiología, 2024)
The treatment of Childhood Apraxia of Speech (CAS) has traditionally focused on enhancing expressive skills such as articulation and intelligibility. Although most of the available strategies promote improvements in speech production, those that improve functional communication have yet to be explored in depth. The objective of this scoping review was to compare the speech-language therapy interventions for CAS that have the most substantial literature support in terms of their focus on promoting functional communication. This review adhered to the PRISMA-ScR guidelines for scoping reviews and considered five interventions frequently mentioned in the literature: The Nuffield Dyspraxia Programme (NDP-3); Physically Restructuring Oral Muscular Phonetic Targets (PROMPT); Dynamic Temporal and Tactile Cueing (DTTC); The Kaufman Speech to Language Protocol (K-SLP); and Integrated Phonological Awareness (IPA). Furthermore, articles published between January 2015 and December 2021 were included from PubMed, WoS, LILACS, Cochrane Library, and Scopus databases. The most relevant findings indicate a lack of generalizability due to small sample sizes, hindering the extrapolation of results related to the intervention of functional communication. This represents a problem in the field of research and could be detrimental to Evidence-Based Practice. In conclusion, an eclectic and holistic approach may be more effective in the treatment of CAS; therefore, we propose a checklist aimed at assessing interventions based on their indicators of functionality.